Quantitative mapping of mRNA 3' ends in Pseudomonas aeruginosa reveals a pervasive role for premature 3' end formation in response to azithromycin. - Salini Konikkat; Michelle R Scribner; Rory Eutsey; N Luisa Hiller; Vaughn S Cooper; Joel McManus (PLoS Genetics)
Pseudomonas aeruginosa produces serious chronic infections in hospitalized patients and immunocompromised individuals, including patients with cystic fibrosis. The molecular mechanisms by which P. aeruginosa responds to antibiotics and other stresses to promote persistent infections may provide new avenues for therapeutic intervention. Azithromycin (AZM), an antibiotic frequently used in cystic fibrosis treatment, is thought to improve clinical outcomes through a number of mechanisms including impaired biofilm growth and quorum sensing (QS). The mechanisms underlying the transcriptional response to AZM remain unclear. Here, we interrogated the P. aeruginosa transcriptional response to AZM using a fast, cost-effective genome-wide approach to quantitate RNA 3' ends (3pMap). We also identified hundreds of P. aeruginosa genes with high incidence of premature 3' end formation indicative of riboregulation in their transcript leaders using 3pMap. AZM treatment of planktonic and biofilm cultures alters the expression of hundreds of genes, including those involved in QS, biofilm formation, and virulence. Strikingly, most genes downregulated by AZM in biofilms had increased levels of intragenic 3' ends indicating premature transcription termination, transcriptional pausing, or accumulation of stable intermediates resulting from the action of nucleases. Reciprocally, AZM reduced premature intragenic 3' end termini in many upregulated genes. Most notably, reduced termination accompanied robust induction of obgE, a GTPase involved in persister formation in P. aeruginosa. Our results support a model in which AZM-induced changes in 3' end formation alter the expression of central regulators which in turn impairs the expression of QS, biofilm formation and stress response genes, while upregulating genes associated with persistence.